Antioxidant and regulatory role of mitochondrial uncoupling protein UCP2 in pancreatic beta-cells - Ježek, P; Olejár, T; Smolková, K; Ježek, J; Dlasková, A; Plecitá-Hlavatá, L; Zelenka, J; Špaček, T; Engstová, H; Pajuelo Reguera, D; Jabůrek, M (Physiological research, 2014)
Research on brown adipose tissue and its hallmark protein, mitochondrial uncoupling protein UCP1, has been conducted for half a century and has been traditionally studied in the Institute of Physiology (AS CR, Prague), likewise UCP2 residing in multiple tissues for the last two decades. Our group has significantly contributed to the elucidation of UCP uncoupling mechanism, fully dependent on free fatty acids (FFAs) within the inner mitochondrial membrane. Now we review UCP2 physiological roles emphasizing its roles in pancreatic beta-cells, such as antioxidant role, possible tuning of redox homeostasis (consequently UCP2 participation in redox regulations), and fine regulation of glucose-stimulated insulin secretion (GSIS). For example, NADPH has been firmly established as being a modulator of GSIS and since UCP2 may influence redox homeostasis, it likely affects NADPH levels. We also point out the role of phospholipase iPLA2 isoform gamma in providing FFAs for the UCP2 antioxidant function. Such initiation of mild uncoupling hypothetically precedes lipotoxicity in pancreatic beta-cells until it reaches the pathological threshold, after which the antioxidant role of UCP2 can be no more cell-protective, for example due to oxidative stress-accumulated mutations in mtDNA. These mechanisms, together with impaired autocrine insulin function belong to important causes of Type 2 diabetes etiology.
Keywords: Insulin; Gene Expression Regulation; oxidační stres; antioxidancia; Glucose; Mitochondria; inzulin; reaktivní formy kyslíku; iontové kanály; glukosa; Uncoupling Protein 2; mitochondriální proteiny; oxidace-redukce; Ion Channels; Mitochondrial Proteins; Reactive Oxygen Species; kultivované buňky; lidé; Antioxidants; Humans; regulace genové exprese; beta-buňky; Cells, Cultured; Insulin-Secreting Cells; Oxidation-Reduction; Oxidative Stress; uncoupling protein 2; mitochondrie